Recent Progress in Fiber-Optic Communication - Pant, Devesh; Malik, Dewesh; Dudeja, Deepak (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
The most latest and advanced mode of data communication which involves, transmitting information from one place to another by flashing/sending pulses of light through an optical fiber can be termed as fiber optic communication. The light (the media of transmission) forms an electromagnetic carrier wave, modulated according to the carrier needs. The optical fibers have revolutionized the data comm.Industry by attaining higher data bit rate of communication speeds over 100 peta-bits per second using these modes of fiber optic communication only.